Methodological problems of modern philosophy of education - Melnik, Olga (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2014)
Methodological problems in the study of philosophy education. It is proved that the philosophy of education is an area of interdisciplinary research, which lies at the intersection of philosophy, pedagogy and practical education. It was demonstrated that there are many problems of educational theory and practice, as well as the education system, which cannot be solved without a philosophical understanding, philosophical reflection, without serious theoretical justification in the general context of the development of world civilization in general and in our country in particular. The subject of philosophy of education, from the author’s point of view is: 1) the solution of the complex epistemological, philosophical-anthropological, cultural, ethical, and other problems; 2) theoretical search in the field of education development strategy, define its objectives and principles of value, the principles of formation educational content, etc.